Blue Lock. 12 - Kaneshiro, Muneyuki (Kodansha USA Publishing, LLC, 2024)
"After making it through the grueling Second Selection, Isagi and the remaining thirty-four strikers prepare for their next challenge, a match against the current U-20 Japan team. At stake: a chance to represent Japan on the world stage as part of the U-20 team. However, with only eleven spots available on the Blue Lock team, Isagi must first clear tryouts if he is to keep his dreams alive. Can he assert his place among the best of the best?!"--